Describing Work Readiness in Psychology Students: Insights from an Indonesia University - Irma Dwiratnasari; Fauziah Rahmawati; Santi Susanti (Indonesian Scientific Publication, 2026)
In today’s competitive labor market, universities must prepare students to meet evolving workplace demands. Work readiness is a multidimensional construct involving personal characteristics, organisational acumen, work competencies, and social intelligence, which differ among individuals. This study aims to describe the level of work readiness of students at the Faculty of Psychology, UNIBI. This study used quantitative and descriptive approaches. Data were collected in May 2025 through an online questionnaire distributed to all students of the Faculty of Psychology from the Class of 2021-2024, ensuring equal opportunity to participate. The study subjects were 115 students from the class of 2021-2024, selected using stratified random sampling. The instrument used was the Work Readiness Scale (WRS) by Caballero, which has been adapted into Indonesian by Rahmawati (2021). The instrument’s validity was examined using corrected item–total correlation. Reliability analysis with Cronbach’s Alpha yielded 0.924, indicating high internal consistency. Data were analyzed descriptively. Score categories (very low to very high) were determined using predefined cut-off score intervals based on the total score range. The results showed that students' work readiness was in the moderate category (41,7%). Organisational acumen is dimension with the highest score, while the social intelligence dimension is the lowest. These findings indicate that students have adequate job readiness, particularly in their understanding and attitudes toward organizations, but still need strengthening in social and interpersonal skills. Therefore, curriculum development should emphasize practical learning experiences to enhance students’ applied competencies and interpersonal readiness for the workplace.